2012
DOI: 10.1080/17458080.2012.736639
|View full text |Cite
|
Sign up to set email alerts
|

Ion beam fluence induced variation in optical band-gap of ZnO nanowires

Abstract: The phenomenon of band-gap engineering of ZnO inserts new platforms to its application base. A similar effort of engineering the optical band-gap of ZnO by ion beam irradiation has been put forwards via this study. We synthesised ZnO nanowires using polycarbonate track-etched membranes as templates. The effect of 50 MeV Li 3þ ion beam (different fluence) on the band-gap of synthesised ZnO nanowires have been studied from Tauc plot and the decrease in the optical band-gap with increase in the radiation fluence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…ion irradiated nanowires Planes Pristine 3 9 10 11 ions/cm 2 1 9 10 12 ions/cm 2 3 9 10 12 ions/cm 2 spectra that area under the absorption spectra increased with increase in ion beam fluence. In post-irradiation cases, similar effect was reported in earlier studies [30,31]. The absorption edge observed around 600 nm for the pristine case varied to around 770 nm corresponds to nanowires.…”
Section: Optical Propertiessupporting
confidence: 88%
“…ion irradiated nanowires Planes Pristine 3 9 10 11 ions/cm 2 1 9 10 12 ions/cm 2 3 9 10 12 ions/cm 2 spectra that area under the absorption spectra increased with increase in ion beam fluence. In post-irradiation cases, similar effect was reported in earlier studies [30,31]. The absorption edge observed around 600 nm for the pristine case varied to around 770 nm corresponds to nanowires.…”
Section: Optical Propertiessupporting
confidence: 88%
“…5c). A similar reduction in the optical bandgap was also observed in the ZnO nanowires, 50 where the origin of the bandgap reduction is attributed to structural modication caused by the implanted ions. In our study, the dominant reduction was found at the highest dose in the Ag + ionimplanted ZnO lms, which is related to the highest damage as shown in Fig.…”
Section: Optical Behavioursupporting
confidence: 64%
“…The formation of new phases is not observed. The change in the crystal structure is explained by an increase in the contribution of thermal vibrations in the lattice arising in interaction of incident ions with lattice atoms ZnО-nanowires 100 nm Li +3 , 50 MeV A. Kaur et al [33] A change in the optical characteristics is observed. An improvement in the optical properties of up to 50% at an irradiation dose of 3 × 10 13 ion cm −2 is established.…”
Section: Discussionmentioning
confidence: 99%
“…Then it was followed by investigation of properties of metallic nanostructures without removing the polymer matrix. Only separate experimental data [25,26,33] on the influence of lowenergy beams of heavy accelerated ions on the structure and transport properties of Zn nanotubes are given in the literature. This fact motivates us to conduct research in this direction, particularly, to study the effect of irradiation with Kr +14 and Xe +22 ions, with an energy of 1.75 MeV/nucleon on structural properties of Zn nanotubes.…”
Section: Introductionmentioning
confidence: 99%